USER EXPERIENCE AND OPPORTUNITIES IN THE USE OF VOICE ASSISTANTS IN INTERACTIVE MARKETING COMMUNICATIONS: AMAZON ALEXA, GOOGLE HOME, APPLE SIRI, YANDEX ALICE - L. G. Akhmaeva (Вестник университета)
The emergence, development, problems, prospects and statistics of the use of voice assistants in interactive marketing communications have been considered. The use of voice assistants as an interface of interaction with electronic equipment is a new, dynamically developing trend, covering all spheres of human activity. The relevance of the studied problem lies in the fact that the integration of advertising in voice assistants in the near future will affect all types of business in one way to another and become an integral part of a successful advertising campaign: these are the most effective interactive marketing communications of the future. The author’s recommendations on the use of voice assistants in interactive marketing communications have been given.